2015
DOI: 10.1111/febs.13408
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct conformational states of Mycobacterium tuberculosis virulent factor early secreted antigenic target 6 kDa are behind the discrepancy around its biological functions

Abstract: Early secreted antigenic target 6 kDa (ESAT‐6) and culture filtrate protein 10 kDa (CFP‐10) are complex proteins secreted by Mycobacterium tuberculosis that play a major role in the pathogenesis of tuberculosis. However, studies focusing on the biological functions of ESAT‐6 led to discordant results and the role of ESAT‐6 remains controversial. In the present study, we aim to address a potential explanation for this discrepancy and to highlight the physiological impact of two conformational states of ESAT‐6. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 48 publications
(119 reference statements)
2
30
1
Order By: Relevance
“…Our findings were contradicted by prior work suggesting that ESAT-6 alone directly lyses membranes by functioning as a secreted pore-forming protein (15,18,28,34). We were puzzled by this discrepancy particularly because we too had previously found that the widely used, commercially prepared recombinant ESAT-6 [from Biodefense and Emerging Infections (BEI) Research Resources Repository] mediated hemolysis and so did the rESAT-6 we prepared using the published protocol (44).…”
Section: Esx-1-dependent Hemolysis Is Accompanied By Membrane Disruptcontrasting
confidence: 69%
See 3 more Smart Citations
“…Our findings were contradicted by prior work suggesting that ESAT-6 alone directly lyses membranes by functioning as a secreted pore-forming protein (15,18,28,34). We were puzzled by this discrepancy particularly because we too had previously found that the widely used, commercially prepared recombinant ESAT-6 [from Biodefense and Emerging Infections (BEI) Research Resources Repository] mediated hemolysis and so did the rESAT-6 we prepared using the published protocol (44).…”
Section: Esx-1-dependent Hemolysis Is Accompanied By Membrane Disruptcontrasting
confidence: 69%
“…In contrast, those that did not use the detergent step reported ESAT-6 to be devoid of cytolytic activity (Table 1). Of note, both we and others (34) have found that recombinant CFP-10 preparations (including from BEI Resources) fail to lyse cells despite being subjected to the identical detergent wash step to that for ESAT-6. This result suggests that any residual detergent was removed during the subsequent wash and dialysis steps in the case of CFP-10 but not ESAT-6 because of tighter binding of detergent to the latter protein.…”
Section: Esx-1-dependent Hemolysis Is Accompanied By Membrane Disruptmentioning
confidence: 59%
See 2 more Smart Citations
“…The ASB-treated and non-treated ESAT-6 showed two distinct conformational states and presented opposing effects on mycobacterial infectivity, macrophage survival, interferon -γ secretion and pore formation (Refai et al, 2015). This observation suggests that the heterodimer of ESAT-6/CFP-10 may be dissociated by a mechanism other than acidification and N-α-acetylation.…”
Section: Unanswered Questionsmentioning
confidence: 99%